Imām Al-Ghazālī Thoughts on Islamic Politics: A Study of The Values of Islamic Education - Khamim Khamim; Muhammad Lutfi Hakim; Mochammad Najmul Afad (AT-TURATS, 2021)
This article discusses Imām Al-Ghazālī’s thoughts regarding politics in Islam, the socio-political conditions behind it, and the values of Islamic education contained in it. This discourse is urgent because seeing the political phenomenon in Indonesia is very worrying after the collapse of the authoritarianism regime during the Old Order era. This paper uses a type of literature research using some of the works of Imām Al-Ghazālī as the primary source. The socio-political conditions underlying the beginning of Imām Al-Ghazālī’s writings related to Islamic politics were the weak understanding of society’s religion and disintegration in the political field of Muslims at that time. From some of his works, there are four themes studied by Imām Al-Ghazālī regarding politics in Islam, namely amar ma’rūf nahī munkar in politics, the origin of the emergence of a nation, theories about state leadership, sources of power and authority of the head of state. As for the values of Islamic education contained in Imām Al-Ghazālī’s thoughts regarding politics in Islam, namely amar ma’rūf nahī munkar, power comes from God, the authority of leaders in matters of the world and the hereafter, mutualism between the people and leaders, mature, intelligent, free, male, a descendant of Quraish, healthy hearing or vision, real power, guidance, knowledge, and being careful in doing things. The fourteen values of Islamic education above include the spiritual dimension, the cultural dimension, and the intelligence dimension.